Linguoculturological Analysis of Proverbs and Sayings in the Russian and Uzbek Languages - Mustafoyeva Lobar Maxmutovna (Researchparks Publishing, 2022)
Linguoculturology focuses primarily on the content side of proverbs and sayings, and in this regard, it uses data from other humanities. The article presents a comparative analysis of proverbs expressing the specific characteristics of Russian and Uzbek linguistic cultures. Russian proverbs and sayings containing the names of food products are used as a source of material for the dictionary